To the question of formation and introduction of model of anti-corruption behaviour of officials on law enforcement in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The corruption problem has obtained a massive character and concerned all the spheres of social life. Moreover, the gist of corruption is not laying in the bribery or corruptibility of persons from the state sector, but it is laying in the disintegration of social system, including the system of state power. The article considers the question which is connected with the Code of officials behavior, the question of forming and introducing the model of anti-corruption behavior of specified persons in the Republic of Kazakhstan. The author depicts the state of legislation and some practical problems, and furthermore the author suggests a row of measures which will support the current process.Key words: anti-corruption behavior, officials, legislation, standard, strategy.